Asymmetric Localization and Distribution of Factors Determining Cell Fate During Early Development of Xenopus laevis - Sindelka, Radek; Sidova, Monika; Abaffy, Pavel; Kubista, Mikael (Results and problems in cell differentiation, 2017)
Asymmetric division is a property of eukaryotic cells that is fundamental to the formation of higher life forms. Despite its importance, the mechanism behind it remains elusive. Asymmetry in the cell is induced by polarization of cell fate determinants that become unevenly distributed among progeny cells. So far dozens of determinants have been identified. Xenopus laevis is an ideal system to study asymmetric cell division during early development, because of the huge size of its oocytes and early-stage blastomeres. Here, we present the current knowledge about localization and distribution of cell fate determinants along the three body axes: animal-vegetal, dorsal-ventral, and left-right. Uneven distribution of cell fate determinants during early development specifies the formation of the embryonic body plan.
Keywords: proteiny Xenopus; Body Patterning; Animals; Asymmetric Cell Division; Xenopus laevis; zvířata; Xenopus Proteins; asymetrické buněčné dělení; rozvržení tělního plánu